Mesenchymal Stromal Cells and Exosomes: Progress and Challenges - Forsberg, Matthew H.; Kink, John A.; Hematti, Peiman; Capitini, Christian M. (Frontiers in Cell and Developmental Biology, 2020)
Due to their robust immunomodulatory capabilities, mesenchymal stem/stromal cells (MSCs) have been used as a cellular therapy for a number of human diseases. Part of the mechanism of action of MSCs is due to production of extracellular vesicles (EVs) that contain proteins, nucleic acids, and lipids that transmit signals to recipient cells that change their biologic behavior. This mini review briefly summarizes the development of MSCs as a treatment for human diseases as well as describes our present understanding of exosomes; how they exert their effects on target cells, and how they are differentiated from other EVs. The current treatment paradigm for acute radiation syndrome (ARS) is discussed, and how MSCs and MSC derived exosomes are emerging as treatment options for treating patients after radiation exposure. Finally, a consideration is given to how these cell-based therapies could possibly be deployed in the event of a catastrophic radiation exposure event.